DAMPAK PEMBANGUNAN JALAN TOL TERHADAP EKONOMI DAN KEUANGAN DAERAH - Aldillah Arumandani; Fauziah Zen (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2023)
The development of toll roads is one of The Government of Indonesia's priority programs to improve regional connectivity and boost economic growth. This thesis aims to evaluate the impact of toll road from 2011 to 2019 on the local economy and municipalities' revenues using the staggered Difference-in-Difference method. The results show that toll roads have no significant impact on GRDP per capita but positively impact local revenue at a weak significance level. The analysis of regional groups shows a negative and significant impact on GRDP per capita in Indramayu, Subang, and Majalengka Regency. In contrast, the City of Binjai, Tebing Tinggi, and Serdang Bedagai Regency receive a positive impact from the toll road on Local Revenue. Local government spending does not have a significant impact on GRDP/capita and Local revenue, while the accommodation and food and beverage sector has a positive and significant impact both on GRDP/capita and Local Revenue. The findings provide input for the Government to improve the quality of government spending and foster the potential of the tourism industry. In addition, the Government needs to synergize the implementation of toll road development with other development programs, such as the linked industrial zone, to capture the potential benefits of the toll road.